PEMBENAHAN PENCATATAN TRANSAKSI KEUANGAN PADA BISNIS KULINER DI DESA KARANGSALAM, BATURRADEN - Herwiyanti, Eliada; Warsidi, Warsidi; Faturokhman, Agus; Dewi, Meutia Karunia (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This community service activity was carried out with the aim of improving the recording of financial transactions in culinary businesses in Karangsalam Village, Baturraden. This activity was motivated by the need for culinary business actors for easy access and availability of financial data to make it easier to find out the financial condition of their business. The community service activity was carried out after the Community Service Team discussed with Partners to ensure the right tools and technology to be selected and implemented. The results of the discussion concluded that Partners could be assisted by implementing point of sales (POS) tools and technology. The implementation of POS tools and technology in Partner businesses is carried out in several stages, the first stage related to the introduction of hardware and software, the second stage related to the trial implementation accompanied by training from the Community Service Team, and the third stage related to the use of devices accompanied by evaluation and monitoring from the Community Service Team. After Partners successfully operated the devices provided, now the recording of culinary business financial transactions is better. Currently, business actors can easily and quickly monitor the movement of stock, see cash in and out, and find out the financial position of their business. Thus, this community service activity has succeeded in solving the problems of recording financial transactions experienced by Partners.